SAMARQAND VILOYATI O‘RTA MAXSUS, KASB-HUNAR TA’LIMI SOHASIDAGI XALQARO ALOQALARI (1991-2016 YY). - Fayzullayeva Shaxnoza Baxriddinova (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article analyzes the establishment, development, and shortcomings of vocational colleges in the Samarkand region during the years of independence, based on cooperation with international organizations such as the UN, the World Bank, the European Bank for Reconstruction and Development, and the Asian Development Bank.